LAJU PELEPASAN DIAZINON DARI MIKROKAPSUL BERBASIS MELAMIN FORMALDEHID (Jurnal Bahan Alam Terbarukan, 2013)
The microcapsules containing diazinon as the core material and melamine formaldehyde as the membrane material have been synthesized by in situ polimerization method. The microcapsule membrane on this researches was modified in two types, the first, melamine formaldehyde (MF) and the second types, melamine formaldehyde added with sodium dodecyl sulphate and polyvinyl alcohol (MF-SDSPVA). This research aims to study the effect of pH and temperature on the release rate of diazinon in aqueous medium. The results showed that the pH and temperature has little effect on the release rate of diazinon from microcapsule based on melamine formaldehyde. This is due to the diffusion through the microcapsule membrane is not influenced by the pH and temperature of the solution outside of microcapsule.